KONTEKSTUALISASI TEOLOGI MODERN Kritik Hassan Hanafi terhadap Teologi Tradisional - Muhammad Taufik (UIN Sunan Kalijaga Yogyakarta, 2019)
In the past theological differences have also been responded to the same as those above, there were those who responded normally there were sometimes disputes. Just how should respond to the differences wisely, because the principle of differences in understanding the concept of theology is normal. Hassan Hanafi, a professor at Cairo University, argued that one of his arguments was that he tried to criticize traditional theology which, according to him, was too central to theological theology. According to him, traditional theology is too monotonous, only talking about the affairs of the